Perceived skill gaps of fisheries extension officers vis-Ã -vis shrimp aquaculture - Kumaran, M; Vimala, D D; Nagarajan, S (Indian Journal of Fisheries, 2012)
Efficient and effective fishery extension officers (FEO) are expected to keep themselves updated on the subject matterthey deal and related aspects. A skill gap analysis was carried out with 33 important competencies required for the fisheriesextension personnel on a dichotomous importance vs competence continuum. The results indicated that higher level ofskill gaps were expressed in shrimp disease diagnosis and management, conducting farm demonstrations, preparation ofextension aids using information communication technologies (ICT), monitoring of soil and water quality parameters andselection of quality shrimp seeds. The respondents were of the perception that research and extension linkage which isvital for capacity enhancement of extension personnel, technology refinement, dissemination and feedback is to be improvedin fisheries sector. In the absence of an efficient mechanism to coordinate research and extension systems, the studysuggested that the research institutions may develop appropriate capacity building modules by incorporating both technicaland extension subjects for training the FEOs in all the maritime states so that location-specific technological issues couldbe focused. The study also recommended that ICT aided tools like expert systems may be developed and employed forenhancing the capacities of the fishery extension officers.